Implications of Information Technology Integration for the Development of Islam in the Modern Era: Implikasi Integrasi Teknologi Informasi Terhadap Perkembangan Agama Islam Dalam Era Modern - Sandi Kurniawan (Averroes: Journal for Science and Religious Studies, 2024)
Background: This research makes a new contribution by proposing a framework for technology integration in Islamic education based on the values of the Quran and Hadith. The integration of technology in Islamic education presents both challenges and opportunities. Methode: The research method of this study is qualitative with a systematic literature study model. The data collected was analysed using thematic analysis techniques to identify relevant patterns and themes. Furthermore, this study developed a prototype of Islamic value-based digital implication, which was trialled in several educational institutions. Main Findings: This research reveals that technology, particularly through e-learning platforms, mobile applications, and social media, has brought about significant transformations in Islam by increasing accessibility, interactivity, and flexibility, particularly in education. Contribution:  This research makes an important contribution by proposing a framework for technology integration in Islam that is based on the values of the Qur'an and Hadith. The proposed framework encompasses not only technical and pedagogical dimensions, but also places significant emphasis on ethical and spiritual aspects. Conclusion: The research also offers concrete solutions to address challenges such as the digital divide and the loss of traditional values through technology-based curriculum design aligned with Islamic principles, thus providing both academic and practical benefits.